ANALISIS ALIRAN RANTAI PASOK JAMUR TIRAM DI SG’S MUSHROOM DESA SUMBERGONDO KACAMATAN BUMIAJI BATU JAWA TIMUR - Wicaksono, Febri; Oktaviani, Dewi Anggun (Agrotechbiz : Jurnal Ilmiah Pertanian, 2024)
Supply chain management is the activity of processing raw materials into goods in process or semi-finished goods and finished goods then sending these products to consumers through the distribution system. The supply chain itself is a complex network consisting of complex suppliers, producers, distributors, retailers and consumers. This research took place at SG'S Mushroom which is located at Sumbergondo sub-district. Bumiaji, Batu City. The aim of this research is to determine the flow and mechanism of the supply chain at SG'S Mushroom so that it can be used as input in determining the appropriate supply chain channels and mechanisms for SG'S Mushroom. The data used is primary data and secondary data and analyzed using qualitative descriptive analysis. The conclusion of this research is that the supply chain flow at SG'S Mushroom consists of the flow of goods, the flow of money and the flow of information which are interconnected. The supply chain mechanism at SG'S Mushroom consists of suppliers, manufacturers, distributors, retailers and consumers. Suppliers at SG'S Mushroom consist of sengon powder suppliers, lime suppliers, rice bran suppliers, plastic suppliers, seed suppliers, and ring and cap suppliers. The manufacturer at SG'S Mushroom is SG'S Mushroom itself. Distributors at SG'S Mushroom consist of collector distributors and CV Arjuna partner distributors. Retailers at SG'S Mushroom consist of ratailer melijo and shop retailers get oyster mushrooms from distributors and souvenir shop retailers get oyster mushrooms from partner distributor CV Arjuna. Lastly is the final consumer, SG'S final consumer gets oyster mushrooms that have been processed or raw. If oyster mushrooms have been processed, consumers get them from gift shops. If oyster mushrooms are still raw, consumers can get them from melijo retailers and stall retailers or get them directly from SG'S Mushroom. Keywords: Supply Chain Flow, Oyster Mushroom